Multiorgan and Renal Tropism of SARS-CoV-2 - Puelles, Victor G; Lütgehetmann, Marc; Lindenmeyer, Maja T; Sperhake, Jan P; Wong, Milagros N; Allweiss, Lena; Chilla, Silvia; Heinemann, Axel; Wanner, Nicola; Liu, Shuya; Braun, Fabian; Lu, Shun; et al. (The New England journal of medicine, 2020)
In this autopsy series, the authors found that SARS-CoV-2 has an organotropism beyond the respiratory tract, including the kidneys, heart, liver, and brain. They speculate that organotropism influences the course of Covid-19 disease and, possibly, aggravates preexisting conditions.